Pelatihan menu sehat balita dalam upaya pencegahan stunting di Desa Ranah Singkuang Kecamatan Kampar - Deviona Deviona; Nelvia Nelvia; Chairul Chairul; Yunandra Yunandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Ranah Singkuang is one of 10 villages classified as stunting villages in the Kampar regency area with a percentage of 24%. The Kampar District Government has done prevention programs on stunting condition from 2018 to 2019. If not treated immediately, the condition of stunting will affect the quality of human resources in the future. The condition of stunting causes children not to grow normally, low IQ, susceptible to infectious diseases as a result of low productivity, and difficulty competing in the world of work. The purpose of this community service activity is the transfer of knowledge to the community in Ranah Singkuang village, increasing the knowledge and ability of village community in terms of processing various kinds of fish-based products that have high nutritional values that are salable in the market in order to boost the community’s economy, provide knowledge about children's health by providing education to the community and training children's healthy menus so that their appetite increases. The result achieved from this community service activity are that the community understands more about the importance of nutrition for toddlers especially before the age of 1000 days and the community can process fish-based food, so that stunting problems in the village can be prevented.